ANALISIS PENGENDALIAN PRODUK CACAT DENGAN METODE FOUR QUALITY CONTROL (4QC) TOOLS - HERY PURNOMO; LILIA PASCA RIANI (Jurnal Akademika, 2018)
The purpose of this study is to determine the extent to which the control of defective products in PT Bisi International Tbk. Kediri, a producer of corn seeds in Kediri Regency. The methods used are Historam, Pareto Diagram, P-Chat 3 sigma control chart and Cause Effect diagram at the production stage. The results showed that by using the Histogram graph, it can be concluded that the number of product defects is mostly in the process of Ear Shortir, pareto diagram shows 69% disability is on the type of seed that is too young and corn seed is less perfect, so with the mitigation of both types of defect, the company can reduce product defect rate by 69%. On the 3 sigma P Chart, it is known that observations 2 and 7 are above the upper control limit, and at 8th observations are below the lower control limits. Analysis of Cause Effect diagram shows there are 6 main sources of causes of product defects, namely from aspects of HR, Equipment, Procedure, Material, and other causes. Keywords: Histogram, Pareto, P-Chart 3 Sigma, Causse Effect, Produk Cacat.